GLOBAL ENVIRONMENTAL INSTITUTIONS - DeSombre, Elizabeth R. ([S.l.] : ROUTLEDGE, 2024)
Global Environmental Institutions provides the most accessible and succinct overview of the major global institutions attempting to protect the natural environment, describing their creation and operation, decision-making processes, interactions with other institutions, and impact. Fully updated throughout, this third edition maintains the clear structure of previous editions, examining the underlying causes of global environmental problems creation of global environmental institutions effectiveness of action undertaken by these institutions Providing an overview of the United Nations Environment Programme alongside other entities that play important roles in global environmental governance, this book examines institutions by issue area and introduces organizations with a specific focus on protecting endangered species and biodiversity, the atmosphere, the ocean environment, and regulating the transboundary movement of hazardous substances. Drawing on the latest scholarship, and written by an acknowledged expert in the field, this study is essential reading for students of environmental politics and international organizations.
Keywords: POLITICAL SCIENCE / General; POLITICAL SCIENCE / International Relations / General; POLITICAL SCIENCE / NGOs (Non-Governmental Organizations); Environmental policy -- International cooperation; Environmental management -- International cooperation; Environmental sciences -- Societies, etc